Translation Revision and Post-editing: Industry Practice and Cognitive Processes - Book review - Li, Yi (English Studies at NBU, 2022)
Book Details: Title: Translation Revision and Post-editing: Industry Practice and Cognitive Processes Editors: Maarit Koponen, Brian Mossop, Isabelle S. Robert, Giovanna Scocchera Publisher: Routledge, 294 pages Year of publication: 2020 ISBN: 9781003096962